Electrocatalytic Properties of Fe-Cu Composites Prepared on the Basis of the Reduced Copper (II) Ferrite - Vissurkhanova, Ya.A.; Ivanova, N.M.; Soboleva, Y.A.; Abulyaissova, L.K.; Minaev, B.F. (Journal of Applied Solution Chemistry and Modeling, 2022)
Copper ferrite (CuFe2O4) samples were prepared by the co-precipitation method without and in the presence of a polymer stabilizer (polyvinyl alcohol, PVA) followed by heat treatment at 500, 700, and 900°C and electrochemical reduction. The structure and morphological features of the samples were investigated by X-ray phase analysis and electron microscopy. It was established that copper (II) ferrite is reduced in an electrochemical system with the formation of Fe-Cu composites with different content of reduced metals, which is influenced by the heat treatment temperature. Copper ferrite prepared with the use of the polymer stabilizer is partially reduced during thermolysis, additionally in an electrochemical cell. The Fe-Cu composites were employed as electrocatalysts in the electrohydrogenation of p-nitrobenzoic acid and exhibited good activity in this process. To study the interaction in the CuFe2O4 + PVA complexes, the quantum-chemical calculations were performed using the density functional theory methods for the simplified metal-containing systems (atoms and ions of copper (II), iron (III), Cu2, Fe2 molecules) as well as dimers and trimers modeling the structure of polyvinyl alcohol.